The identification of training transfer factors among academic staffs of UiTM - Wan Abd Aziz, Wan Mohd Amin; Ibrahim, Mamat; Nik Sarina, Nik Md Salleh; Mohd Sallehin, Jusoh (2017)
Research related to factors affecting transfer of training in the public universities in Malaysia is extremely limited. Hence, this article examines the impact of employee readiness factors (attitude, organizational commitment, motivation to learn and motivation to learn), training design factors (error management and perceived importance) and work environmental factors (supervisor’s role and opportunity to use) on transfer of training. Data were collected from 238academic staffs of UiTM who participated in four training programs. The Structural Equation Modelling technique was used to test the hypotheses derived from the literature. The findings revealed that attitudes, error management, supervisor’s role and opportunity to use have a significant impact on the transfer of training. Contrary to expectations, motivation to transfer did mediate partially between error management, opportunity to use and transfer of training. The implications of the results and limitations of the study are also noted, along with suggestions.